PENGARUH KOMITMEN ORGANISASI, KEPUASAN KERJA DAN KEPERCAYAAN TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN SORONG - Alhamid, Yaser Arafat; Pahmi, Pahmi; Irwan, Andi (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine and analyze the influence of organizational commitment, job satisfaction, and trust on employee performance at the Regional Secretariat of Sorong Regency. Organizational commitment, job satisfaction, and trust are crucial factors believed to affect the quality and productivity of employees. These variables play an important role in creating a conducive work environment, building motivation, and enhancing employees' sense of responsibility in carrying out their duties. The research employs a quantitative approach with a survey method involving employees at the Regional Secretariat of Sorong Regency. Data are collected through questionnaires developed based on indicators from each research variable. Data analysis is conducted to determine the extent of the influence of organizational commitment, job satisfaction, and trust, both simultaneously and partially, on employee performance. The results of this study are expected to contribute to the development of human resource management theory, particularly within the context of local government institutions. Furthermore, this research is anticipated to serve as a reference for the management of the Regional Secretariat of Sorong Regency in formulating strategic policies aimed at improving employee performance by strengthening organizational commitment, increasing job satisfaction, and building trust in the workplace.